Books from lost libraries : The Medieval Dioceses of Cenad, Oradea, and Transylvania - PAPAHAGI, Adrian (Presa Universitară Clujeană, 2023)
Cumpărați cartea în format tipărit. This volume discusses extant books, book fragments, and information about lost books connected to the Catholic bishoprics of Cenad, Oradea, and Transylvania before the Reformation. It presents the work of the few identifiable scribes, illuminators and bookbinders active in these dioceses, and the circulation of manuscripts and incunabula to and from these provinces. The period under scrutiny starts in the eleventh century, when the three dioceses were established. Books are mentioned in the eleventh and twelfth centuries, a few manuscripts of disputed origin survive from the twelfth, thirteenth and fourteenth centuries, but only the fifteenth and sixteenth centuries can be relatively well documented through inventories and surviving books. The fate of books is also followed during and after the Reformation, when most medieval collections were scattered or utterly destroyed. The present research complements a recent census of medieval manuscripts in Romanian libraries by adducing as evidence manuscripts of local origin, provenance or relevance kept in foreign libraries. CONTENTS Introduction … 7 The Diocese of Cenad … 15 The Diocese of Oradea … 29 The Diocese of Transylvania … 75 Alba Iulia … 77 Cluj and Cluj-Mănăștur … 99 Bistrița and Jelna … 139 Sebeș … 153 Sighișoara … 165 Târgu Mureș, Șumuleu Ciuc, and the Szekler Region … 177 Satu Mare and Baia Mare … 197 Brașov and Râșnov … 203 Closing remarks … 225 Bibliography … 231 Indices … 263